This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Math021, week 6 Chain Rule Theorem 6.1 (Chain Rule) Let f and g be functions. Then, ( f ◦ g ) ( x ) = f ( g ( x )) g ( x ) proof (sloppy): For all numbers x and h 6 = 0, f ◦ g ( x + h ) f ◦ g ( x ) h = f ( g ( x + h )) f ( g ( x )) h = f ( g ( x )+( g ( x + h ) g ( x ))) f ( g ( x )) g ( x + h ) g ( x ) g ( x + h ) g ( x ) h Thus, ( f ◦ g ) ( x ) = lim h → f ( g ( x )+( g ( x + h ) g ( x ))) f ( g ( x )) g ( x + h ) g ( x ) g ( x + h ) g ( x ) h = lim h → f ( g ( x )+( g ( x + h ) g ( x ))) f ( g ( x )) g ( x + h ) g ( x ) lim h → g ( x + h ) g ( x ) h = lim k → f ( g ( x )+ k ) f ( g ( x )) k lim h → g ( x + h ) g ( x ) h = f ( g ( x )) g ( x ) . Remark 6.2 The chain rule can be presented alternatively as follows: Let u = g ( x ) and y = f ( u ) (a way to present the composite function f ◦ g .). The chain rule becomes dy dx = dy du du dx . Example 6.3 Let y = (2 x + 1) 4 . Evaluate dy dx . solution: Let u = 2 x + 1, then y = u 4 so that dy du = 4 u 3 . On the other hand, u = 2 x + 1 so that du dx = 2 . 1 Combining these results by chain rule, we have dy dx = (4 u 3 )(2) = 8(2 x + 1) 3 . Alternatively, we may let g ( x ) = 2 x + 1, f ( x ) = x 4 . Then, f ◦ g ( x ) = (2 x + 1) 4 and ( f ◦ g ) ( x ) = g ( x ) f ( g ( x )) = (2)(4( g ( x ) 3 )) = 8(2 x + 1) 3 . Example 6.4 Let y = sin( x 2 + 1) . Evaluate dy dx . solution: Let u = x 2 + 1, then y = sin u so that dy du = cos u. On the other hand, u = x 2 + 1 so that du dx = 2 x. By chain rule, dy dx = dy du du dx = 2 x cos u = 2 x cos( x 2 + 1) ....
View Full
Document
 Fall '10
 LUXNU
 Chain Rule

Click to edit the document details